Ultraviolet spectral broadening by stimulated rotational Raman scattering on nitrogen pumped with signal laser injection - Xiangbing Wang; Xiangxu Chai; Ping Li; Bo Zhang; Qihua Zhu; Xiaocheng Tian; Ju Wang; Zhaoyu Zong; Song Zhou; Ke Yao; Sen Li; Junpu Zhao; et al. (Matter and Radiation at Extremes)
We present experimental results on kilojoule ultraviolet laser output with 1% spectral broadening. Through stimulated rotational Raman scattering (SRRS) with signal laser injection, we achieve effective spectral broadening in short-range propagation, with good retention of the original near-field distribution and time waveform. Theoretical calculations show that 2% bandwidth spectral broadening can be achieved by injecting 20 kW/cm2 signal light at 2.2 GW/cm2 flux of the pump laser. In addition, high-frequency modulation in the near field can be effectively avoided through replacement of the original random noise signal light by the controllable signal light. The SRRS in the atmospheric environment excited with signal laser injection can provide wide-band light output with controllable beam quality without long-distance propagation, representing an important potential route to realization of broadband laser drivers.